Quips, quotes and quanta : An anecdotal history of physics - Capri, Anton Z. (New Jersey, World Scientific, 2011)
When a ship's surgeon during a routine episode of bloodletting noticed that the sailors' blood was brighter in the tropics than in the north, he hypothesized that heat was a form of energy. When a young boy tried to visualize what a beam of light would look like by riding alongside it at the same speed, he began thinking along lines that eventually changed our views of space and time. When a student caught hay fever and went to recover on Heligoland, he started a major revolution in physics. These are but just some of the stories covered in this entertaining book that deals with the history of physics from the end of the 19th-century to about 1930. Quips, Quotes and Quanta (2nd Edition) is unique in that it contains anecdotes on physicists creating new ideas. Often the thinking of the creators of what is now called ''modern physics'' is revealed through quotes. Thematic and biographical in nature, this book also includes many personal incidents. This second edition has been revised to include new material: a prologue, epilogue, glossary and chronology, and photographs as well as additional quotes and anecdotes.
Index 232-238p.
Keywords: Anecdotes; History; Physics